Uveitis occurring in a patient with psoriasis during adalimumab therapy: A case report - Qiaoli Zheng; Yingjie Zhu; Hao Cheng; Kejian Zhu (Wolters Kluwer Medknow Publications, 2022)
Here we report a case of a 34-year-old patient with psoriasis who developed uveitis induced by adalimumab. After receiving two subcutaneous injections of adalimumab, the patient suffered from a sudden onset of ocular pain and blurred vision in her left eye, which was diagnosed with acute anterior uveitis. Adalimumab therapy was discontinued and the patient was hospitalised for the treatment of acute anterior uveitis with systemic corticosteroids. This paradoxical adverse event was alleviated after timely interventions and went into remission during a 6-month follow-up period. To the best of our knowledge, this is the first case of uveitis occurring in patients with psoriasis under adalimumab treatment. It indicates that paradoxical uveitis, although rare, is one of the adverse events of adalimumab therapy. Early recognition and prompt intervention would lead to a good outcome.